2022
DOI: 10.3389/fpsyg.2022.1013584
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of the Italian brief version of the multidimensional jealousy scale: Psychometric properties, measurement invariance across gender, and convergent validity

Abstract: IntroductionThe multidimensional jealousy scale (MJS) is among the most internationally used instruments for the assessment of jealousy in its three dimensions: cognitive, emotional, and behavioral. This study aimed to replicate the Italian validation process of the shortened MJS in order to confirm its psychometric properties and measurement invariance across gender.Materials and methodsExploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted in a large sample of adults (n = 2,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…Further analysis of the CFA models revealed good item-factor correlation coefficients, indicating close relationships between the items and the underlying factors of both the dichotomous and rating tests. This finding supports the development of robust constructs for both tests by CFA measures (Diotaiuti et al 2022;Liu et al 2020). Consequently, it can be inferred that the DIFER test successfully captures the multidimensional nature of school readiness, lending further support to its construct validity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further analysis of the CFA models revealed good item-factor correlation coefficients, indicating close relationships between the items and the underlying factors of both the dichotomous and rating tests. This finding supports the development of robust constructs for both tests by CFA measures (Diotaiuti et al 2022;Liu et al 2020). Consequently, it can be inferred that the DIFER test successfully captures the multidimensional nature of school readiness, lending further support to its construct validity.…”
Section: Discussionsupporting
confidence: 81%
“…However, for such studies to yield meaningful and comparable results, it is imperative that the measurement instruments used possess measurement invariance. (Diotaiuti et al 2022). By establishing measurement invariance, researchers gain confidence in comparing and interpreting analytical outcomes, such as latent means, across distant groups and different timeframes (Gygi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This Result is consistent with Costa et al (2015) and Richter et al (2022). Diotaiuit and colleagues conducted a validation study of the Italian version of the multidimensional jealousy scale, which showed that anxiety and jealousy were positively correlated and supported this study (Diotaiuti et al, 2022). According to attachment theory, individuals with attachment anxiety fear abandonment.…”
Section: Discussionsupporting
confidence: 77%
“…The Portuguese version demonstrated strong internal consistency across all sub-dimensions, with Cronbach's alpha values of 0.92 for cognitive jealousy, 0.86 for emotional jealousy, 0.90 for behavioral jealousy, and 0.86 for the total scale. This instrument has been validated for different populations, including the Urdu population [26], Italian population [27], Iranian population [28], Serbian population [29], and Australian population [30].…”
Section: Multidimensional Jealousy Scale (Mjs)mentioning
confidence: 99%